Heat treatment method for improving low-temperature impact toughness of steel

Through the combined process of preheating treatment and final heat treatment, the low-temperature impact toughness of steel for high-ice-grade shaft system is improved, the problem of insufficient low-temperature toughness of materials in the prior art is solved, and higher mechanical properties are achieved and production costs are reduced. Effect.

CN119391946AActive Publication Date: 2025-02-07WUHAN UNIV OF SCI & TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411552743.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

In polar environments, steel materials for high ice-grade shaft systems need to have comprehensive properties such as high and low temperature toughness, strength and fatigue strength, but the prior art is difficult to effectively improve their low temperature impact toughness.

Method used

A combination of preheating treatment and final heat treatment is adopted, including preheating treatment steps: the steel is heated to 840-880℃, insulated for 2-3 hours, then the oil is cooled to room temperature, then heated to 560℃, insulated for 8-10 hours, oil is Cool to room temperature; final heat treatment step: The steel is heated to 840℃ with the furnace, and insulated for 0.5 to 1 hour, then isothermal treatment is in the Ac1 to Ac3 range, and continues to be insulated for 0.5 to 1 hour, then water is cooled to room temperature, and finally heated to 580 to 600 ℃, keep warm for 2 hours, and cool to room temperature at air.

Benefits of technology

Through this heat treatment method, the low-temperature impact toughness of the steel is significantly improved, the mechanical properties requirements of extremely low icebreaker shaft steel are met, and the production cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391946A_ABST
    Figure CN119391946A_ABST
Patent Text Reader

Abstract

The invention provides a heat treatment method for improving low-temperature impact toughness of steel, which comprises the following steps: S1, preheating treatment: heating the steel to 840-880 DEG C, preserving heat for 2-3 hours, and then performing oil cooling to room temperature; the temperature is increased to 560 DEG C, heat preservation is conducted for 8-10 h, and then oil cooling is conducted to the room temperature; s2, final heat treatment is conducted, specifically, the steel is heated to 840 DEG C along with the furnace, heat preservation is conducted for 0.5-1 h, then the steel is cooled to the temperature within the Ac1-Ac3 interval along with the furnace for isothermal treatment, heat preservation continues for 0.5-1 h, and then water cooling is conducted to the room temperature; and finally, the temperature is increased to 580-600 DEG C, heat preservation is conducted for 2 h, and then air cooling is conducted to the And through the composite action of preheating treatment and final heat treatment, the steel can absorb more capacity in the impact process, so that the low-temperature impact toughness of the steel is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ship shafting steel, and in particular to a heat treatment method for improving the low-temperature impact toughness of steel. Background Art

[0002] As conventional exploitable energy sources are gradually depleted, the development and utilization of marine resources has become an inevitable trend in future energy utilization. The polar and deep-sea regions have rich energy reserves and are receiving more and more attention. At the same time, with the gradual opening of the Arctic route, the exploitation of marine resources has gradually developed from shallow seas to deep sea areas and polar high-cold areas, which will greatly promote the demand and development of high-ice-class icebreakers. The natural conditions in the polar regions are harsh, with challenges such as low temperature tests, sea ice obstacles, iceberg attacks, blizzard attacks, fragile ecological environment, polar night troubles, and poor visibility, which place high demands on the performance of related equipment and materials. The ultra-low temperature environment in the polar regions puts forward requirements for key technologies such as low temperature resistance, corrosion resistance, wear resistance, easy welding, and high toughness of materials.

[0003] Therefore, high ice grade shafting steel usually uses special low temperature steel, which must have sufficient low temperature toughness, strength, fatigue strength and other comprehensive properties. Improving the low temperature toughness of shafting materials is the key point for the mechanical properties of ship shafting materials to meet the standards. Therefore, it is necessary to provide a heat treatment method to improve the low temperature toughness of shafting materials. Summary of the invention

[0004] The main purpose of the present invention is to provide a heat treatment method for improving the low temperature toughness of steel. The method can significantly improve the low temperature toughness of steel, especially shaft steel, and meet the mechanical property requirements of shaft steel for ultra-low icebreakers.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A heat treatment method for improving the low-temperature impact toughness of steel comprises the following steps:

[0007] S1. Preheating treatment: heat the steel to 840-880℃, keep it warm for 2-3h, then oil cool it to room temperature; then heat it to 560℃, keep it warm for 8-10h, then oil cool it to room temperature;

[0008] S2, final heat treatment: the steel is heated to 840°C in the furnace, kept at this temperature for 0.5-1h, then cooled in the furnace to a temperature in the range of Ac1-Ac3 for isothermal treatment, kept at this temperature for 0.5-1h, then water-cooled to room temperature; finally heated to 580-600°C, kept at this temperature for 2h, then air-cooled to room temperature.

[0009] The present invention creatively proposes an isothermal quenching process of preheating treatment plus final heat treatment. During the isothermal process, the grains are refined and part of the α phase is retained. High-temperature tempering transforms the residual austenite in the steel into martensite, and finally the room temperature structure is mostly α phase. Various carbides pin the displacement of the grain boundaries, and the high dislocation density interacts with the grain boundaries, effectively hindering the movement of dislocations. The above-mentioned composite action helps to absorb more energy during the impact process, thereby improving the impact toughness of the steel.

[0010] Furthermore, the isothermal treatment temperature in step S2 is 730-770° C. In the final heat treatment process, a temperature above the medium temperature in the range of Ac1-Ac3, i.e., 730-770° C., is selected for isothermal treatment.

[0011] Furthermore, the steel is a shafting steel, and its chemical composition includes, by mass percentage: C 0.3-0.4%, Si 0.17-0.37%, Mn 0.5-0.8%, Cr 1.0-1.7%, Ni 1.2-1.6%, Mo 0.2-0.5%, Cu≤0.25%, S≤0.025%, P≤0.025%, and the rest are iron elements and unavoidable impurities.

[0012] Furthermore, the steel is a shafting steel, and its chemical composition includes, by mass percentage, C 0.36%, Si 0.27%, Mn 0.61%, Cr 1.63%, Ni 1.59%, Mo 0.25%, Cu 0.10%, S≤0.025%, P≤0.025%, and the rest are iron elements and unavoidable impurities.

[0013] The alloy element ratio of the steel is reasonably selected to improve the hardenability and tempering stability, while improving the strength and toughness of the steel. In combination with the heat treatment process of the present invention, the best low-temperature impact toughness can be obtained.

[0014] Compared with the prior art, the heat treatment method of the present invention has at least the following beneficial effects:

[0015] 1. Compared with other high-toughness shafting materials, the moderate Ni content of the composition of the present invention improves low-temperature impact toughness while ensuring yield strength and fatigue strength, while reducing steel production costs;

[0016] 2. The heat treatment process proposed in the present invention includes two steps: preheating treatment and final heat treatment, both of which are indispensable. Through the synergistic effect of preheating treatment and final heat treatment, a composite structure of martensite and ferrite is obtained, which effectively inhibits the formation and expansion of microcracks, thereby improving low-temperature impact toughness and having higher comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying any creative work.

[0018] Figure 1 The scanning electron microscope microstructure photo (left) and -40°C impact fracture morphology photo (right) of the sample in Example 1;

[0019] Figure 2 The scanning electron microscope microstructure photo (left) and -40°C impact fracture morphology photo (right) of the sample in Example 2;

[0020] Figure 3 The scanning electron microscope microstructure photo (left) and -40°C impact fracture morphology photo (right) of the sample in Example 3;

[0021] Figure 4 The scanning electron microscope microstructure photo (left) and -40°C impact fracture morphology photo (right) of the sample in Comparative Example 1 are shown;

[0022] Figure 5 The optical microscopic micrographs of the samples in Examples 1, 2, 3 and Comparative Example 1 are shown, wherein a: the sample in Example 1; b: the sample in Example 2; c: the sample in Example 3; d: the sample in Comparative Example 1;

[0023] Figure 6 They are the IPF and KAM diagrams of Example 2 and Comparative Example 1, wherein (a) and (b) are the IPF and KAM diagrams of Comparative Example 1, respectively, and (c) and (d) are the IPF and KAM diagrams of Example 2, respectively.

[0024] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0027] The present invention provides a heat treatment method for improving the low temperature impact toughness of steel, comprising the following steps:

[0028] S1. Preheating treatment: the steel is gradually heated to 840-880℃, kept at this temperature for 2-3h, and then oil-cooled to room temperature; then the temperature is gradually heated to 560℃, kept at this temperature for 8-10h, and then oil-cooled to room temperature;

[0029] S2, final heat treatment: the steel is rapidly heated to 840°C in the furnace, kept at this temperature for 0.5-1h, then slowly cooled to a temperature in the range of Ac1-Ac3 in the furnace for isothermal treatment. Preferably, the steel is slowly cooled to 730-770°C in the furnace for isothermal treatment, kept at this temperature for 0.5-1h, then water-cooled to room temperature; finally, the temperature is raised to 580-600°C, kept at this temperature for 2h, then air-cooled to room temperature.

[0030] In some embodiments, the steel is a shafting steel, and its chemical composition includes, by mass percentage: C 0.3-0.4%, Si 0.17-0.37%, Mn 0.5-0.8%, Cr 1.0-1.7%, Ni 1.2-1.6%, Mo 0.2-0.5%, Cu≤0.25%, S≤0.025%, P≤0.025%, and the rest are iron elements and unavoidable impurities.

[0031] In some embodiments, the steel is a shafting steel, and its chemical composition includes, by mass percentage: C 0.36%, Si 0.27%, Mn 0.61%, Cr 1.63%, Ni 1.59%, Mo 0.25%, Cu 0.10%, S ≤ 0.025%, P ≤ 0.025%, and the rest are iron elements and unavoidable impurities.

[0032] The present invention reasonably selects the elemental components in the steel, wherein a suitable C content is selected to balance the low-temperature toughness while improving the tensile strength and increasing the cold brittleness of the steel; a suitable Si content is selected to significantly improve the tensile strength and yield strength of the steel, and combined with Mo and Cr elements to improve the oxidation resistance of the steel; a suitable Mn content is selected to be integrated into ferrite, improve the strength of the steel, play a role in solid solution strengthening, and improve the hardenability, which is also beneficial to the desulfurization of the steel; a suitable Cr content is selected to improve the hardenability and tempering stability, and at the same time can improve the strength, hardness and wear resistance of the steel; a suitable Ni content is selected to improve the plasticity and toughness of the steel, and at the same time improve the strength of the steel; a suitable Mo content is selected to improve the hardenability and tempering stability, effectively inhibit the segregation of harmful elements in the steel, refine the grains, and is beneficial to alleviate the high-temperature tempering brittleness; ensuring that the Cu content is less than 0.25wt% can improve the strength and toughness of the steel; both the P element and the S element have an adverse effect on the low-temperature toughness of the steel, and therefore, the contents of P and S are limited to no more than 0.025wt%. This solution significantly improves the low-temperature impact toughness of steel by compounding the above-mentioned element contents in combination with the heat treatment method described in this solution.

[0033] Those skilled in the art should know that the Ac1 temperature is the temperature at which pearlite transforms to austenite when the steel is heated, and the Ac3 temperature is the final temperature at which the steel transforms to austenite when the steel is heated.

[0034] It should be noted that the original material is forged along the axis after smelting, which is conducive to the forming of the shaft and the improvement of impact toughness and fatigue resistance along the axis. In the preheating process of this scheme, the steel is heated to above Ac1 and kept warm for a sufficient time. The Si element in the steel increases the chemical potential of ferrite, prompting C in ferrite to diffuse into the austenite to obtain an austenite structure, and then tempered at 560℃, which is mainly tempered troostite and a small amount of residual austenite. The presence of Ni element expands the austenite phase region. The measured temperature difference between Ac1 and Ac3 of the shafting steel in the above quality range is about 100℃. During the final heat treatment, the upper temperature in the Ac1-Ac3 range is selected for isothermal treatment for 0.5-1h to crystallize the grains and increase the grain boundaries and phase interfaces. At the same time, a part of the ferrite is retained, and the retained part of the ferrite promotes the martensitic transformation. Subsequently, the austenite is transformed into a martensitic structure by cooling at a rate greater than the critical cooling rate (greater than 10℃ / s, less than 100℃ / s water cooling). The tempering temperature is 580-600℃, which transforms the retained austenite into tempered martensite, and finally obtains ferrite and a small amount of martensite structure. This reduces the martensite lath structure and makes the Cr-rich M 23Carbides such as C6 are evenly dispersed and not overly coarsened. Ni inhibits the formation of brittle phase cementite, thereby reducing the core of cracks induced during plastic deformation. After multiple tests, it was found that the dislocation density reached a maximum after tempering at 600°C, and the resulting martensite and ferrite composite structure can effectively inhibit the formation and expansion of microcracks and further improve low-temperature toughness.

[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0036] The mechanical properties test of the steels prepared in all the embodiments and comparative examples of the present invention adopts V-notch specimens to detect the impact toughness, and the impact samples are tested in accordance with the requirements of GB / T 229-2020 "Charpy Pendulum Impact Test Method for Metallic Materials"; the room temperature tensile samples are tested in accordance with GB / T 228.1-202 "Metallic Materials Tensile Test Part 1: Room Temperature Test Method".

[0037] Example 1

[0038] A heat treatment method for improving the low-temperature impact toughness of steel comprises the following steps:

[0039] S1. Preheating treatment: the steel is gradually heated to 840℃, kept at this temperature for 3h, and then oil-cooled to room temperature; then the temperature is gradually heated to 560℃, kept at this temperature for 8h, and then oil-cooled to room temperature;

[0040] S2. Final heat treatment: Rapidly heat the steel to 840℃ with the furnace, keep it warm for 0.5h, then slowly cool it to 770℃ with the furnace for isothermal treatment, continue to keep it warm for 0.5h, then water cool it to room temperature; finally heat it to 600℃, keep it warm for 2h, then air cool it to room temperature.

[0041] The chemical composition of the steel used in this embodiment includes, by mass percentage, C 0.36%, Si 0.27%, Mn 0.61%, Cr 1.63%, Ni 1.59%, Mo 0.25%, Cu 0.10%, and the rest is iron and unavoidable impurities. The Ac1 temperature of the steel used in the thermal simulation experiment is 690°C, and the Ac3 temperature is 793°C.

[0042] After the above process, the sample prepared in Example 1 was tested for detection and mechanical properties, and the microstructure of the sample in Example 1 was observed using a scanning electron microscope (SEM). Figure 1 As shown on the left, the austenite grain boundary can be clearly seen, and the structure is tempered troostite, but the needle-like morphology of martensite has not completely disappeared, and the needle-like outline can still be observed; Figure 1 The right side is a photo of the -40℃ impact fracture morphology. The width of the protruding shear lip area is about 1706μm. The wider the shear lip area, the better the impact toughness.

[0043] Example 2

[0044] This embodiment adopts the same parameters and processes as those of Embodiment 1, with the only difference being that the isothermal treatment temperature in the final heat treatment step is 750°C.

[0045] The samples prepared in Example 2 were tested for mechanical properties, and the microstructure of the samples in Example 2 was observed using a scanning electron microscope (SEM). Figure 2 As shown on the left, the tempered troostite structure is fine and uniform, in which large particles may be the second phase and the striped areas are pearlite lamellae; the widest part of the protruding shear lip area in the right picture is about 1712μm.

[0046] Example 3

[0047] This embodiment adopts the same parameters and processes as those of Embodiment 1, with the only difference being that the isothermal treatment temperature in the final heat treatment step is 730°C.

[0048] The samples prepared in Example 3 were tested for their mechanical properties, and the test results are shown in Table 1. The microstructure of the samples in Example 3 was observed using a scanning electron microscope (SEM). Figure 3 As shown on the left, the number of martensite needle-like morphology is slightly reduced; the right picture is a quasi-cleavage fracture, and the widest part of the shear lip area is measured to be about 1460μm.

[0049] Comparative Example 1

[0050] This comparative example uses the same steel as Example 1, and the heat treatment method only includes preheating treatment: the steel is gradually heated to 840°C, kept warm for 3 hours, and then oil-cooled to room temperature; then gradually heated to 560°C, kept warm for 8 hours, and then oil-cooled to room temperature.

[0051] After the above process, the samples prepared in comparative example 1 were tested and the mechanical properties were tested. The average impact energy at -40°C was only 50J, the tensile strength was 804.5MPa, the yield strength was 936.0MPa, and the elongation after fracture was 18.1%.

[0052] The microstructure of the sample of Comparative Example 1 was observed using a scanning electron microscope (SEM). Figure 4 As shown on the left, the carbide size is larger than that of Example 1, and the austenite grains are coarse; Figure 4 The right is a photo of the -40℃ impact fracture morphology. It can be seen that the lower shear lip area is thinner with a thickness of about 180μm, and the boundary with the river pattern in the radial area is clearly visible, and the toughness is poor.

[0053] Comparative Example 2

[0054] The chemical composition of the steel used in this comparative example includes, by mass percentage, C 0.33%, Si 0.30%, Mn 0.64%, Cr 1.07%, Ni 0.34%, Mo 0.48%, and the rest is iron and inevitable impurities. The chemical composition of the steel is shown in Table 2 by mass percentage. The specific parameters of the heat treatment method are the same as those in Example 1, including only preheating treatment and two steps of preheating treatment and final heat treatment. The mechanical properties after the heat treatment stage S1 and after S2 are tested.

[0055] After preheat treatment S1, the yield strength of the sample at room temperature is 704Mpa, the tensile strength is 841Mpa, and the -40℃ low-temperature impact absorption energy is 35.2J. After S2 treatment, the yield strength is increased to 1066Mpa, the tensile strength is increased to 918.5Mpa, and the -40℃ low-temperature impact absorption energy is increased to 48J. However, the -60℃ low-temperature impact performance decreases after S2. Detailed mechanical properties are shown in Table 3.

[0056] Comparative Example 3

[0057] The chemical composition of the steel used in this comparative example includes, by mass percentage, C 0.35%, Si 0.30%, Mn 0.92%, Cr 1.29%, Ni 0.55%, Mo 0.27%, and the rest is iron and unavoidable impurities, see Table 2. The heat treatment method is the same as that of comparative example 2, and the mechanical properties after the heat treatment stage S1 and after S2 are tested.

[0058] While the tensile properties are improved after S2 heat treatment, the low-temperature impact properties are also improved, but the -40°C low-temperature impact energy is only 25.4 J, which is significantly lower than the impact absorption energy of Examples 1 to 3.

[0059] Comparative Example 4

[0060] The chemical composition of the steel used in this comparative example includes, by mass percentage, C 0.44%, Si 0.24%, Mn 1.15%, Cr 0.22%, Ni 0.36%, Mo 0.07%, and the rest is iron and unavoidable impurities, see Table 2. The heat treatment method is the same as that of comparative examples 2 and 3, and the mechanical properties after the heat treatment stage S1 and after S2 are tested.

[0061] After the S2 treatment, the tensile strength of the comparative example can be increased to 988Mpa, and the yield strength can be increased to 894.5Mpa. The low-temperature impact performance is also improved, but the impact performance is seriously reduced at lower temperatures. Similarly, its toughness is far inferior to the performance of Examples 1 to 3.

[0062] Table 1 Mechanical properties of Examples 1 to 3 (normal temperature tensile and low temperature impact)

[0063]

[0064] Note: A KV is the impact energy of the V-notch specimen, R m is the tensile strength, R p0.2 A is the yield strength, Z is the elongation after fracture, and Z is the reduction of area.

[0065] Table 2 Chemical composition of steel in comparative examples 2 to 4 in percentage by mass

[0066] Serial number C Si Mn Cr Ni Mo Fe and impurities Comparative Example 2 0.33 0.30 0.64 1.07 0.34 0.48 margin Comparative Example 3 0.35 0.30 0.92 1.29 0.55 0.27 margin Comparative Example 4 0.41 0.24 1.15 0.22 0.36 0.07 margin

[0067] Table 3 Mechanical properties of comparative examples 1 to 4 (normal temperature tensile and low temperature impact)

[0068]

[0069] As can be seen from Table 1, the average low-temperature impact absorption energy of -20°C for the steel treated by this scheme in Example 1 is 121.4J, the average low-temperature impact absorption energy of -40°C is 114.2J, and the average low-temperature impact absorption energy of -60°C is 116.0J. The average low-temperature impact absorption energy of -20°C for the steel treated by this scheme in Example 2 is 130.5J, the average low-temperature impact absorption energy of -40°C is 100.6J, and the average low-temperature impact absorption energy of -60°C is 104.3J. The average low-temperature impact absorption energy of -20°C for the steel treated by this scheme in Example 3 is 119.0J, the average low-temperature impact absorption energy of -40°C is 114.8J, and the average low-temperature impact absorption energy of -60°C is 116.1J. The sample in Comparative Example 1 was only preheated without final heat treatment, and the low-temperature impact toughness at -40°C was only 50J / cm 2 , significantly lower than the samples in Examples 1 to 3. The steels used in Comparative Examples 2 to 4 are not within the range of chemical composition described in this scheme. After the heat treatment of the present invention, the low-temperature impact absorption energy above -40°C and the tensile properties at room temperature are improved to varying degrees, indicating that the heat treatment method adopted in this scheme can significantly improve the mechanical properties and low-temperature impact toughness of the steel, especially the low-temperature toughness. After the heat treatment method of the present invention, the improvement is obvious, which is very helpful to improve the comprehensive performance of low-temperature marine shafting materials. However, the low-temperature impact performance of Comparative Examples 2 to 4 is significantly lower than that of Examples 1 to 3. It shows that the steel using the raw material components in Examples 1 to 3 of this scheme has the best low-temperature impact toughness, and still maintains good low-temperature impact toughness at -60°C. It should be noted that Comparative Examples 2 to 4 are only exemplary displays. When the other components are not within the range described in this scheme, the low-temperature impact toughness measured by the samples does not reach the best effect, which will not be repeated here.

[0070] Reference Figure 5These are optical microscopic photos of the metallographic structures of Examples 1, 2, 3 and Comparative Example 1. In the figure, a, b, c, and d are all tempered troostite. Figure 5 (d) shows that the structure of comparative example 1 contains ferrite and cementite. It can be seen from the figure that the structure of example 2 is the most uniform. At the same time, the electron backscatter diffraction method (EBSD) is used to compare the grain size statistics and stress distribution of comparative example 1 and example 2, as shown in FIG. Figure 6 As shown. (a) and (b) are the IPF and KAM diagrams of comparative example 1, respectively, and (c) and (d) are the IPF and KAM diagrams of embodiment 2, respectively. Comparing (a) and (c), it is obvious that the grain size of embodiment 2 in (c) is smaller; according to statistics, there are 6205 grains on this surface, with equivalent circle diameters ranging from 2.14 to 24.08 μm, and most of the sizes are in the range of 2.14 to 6.53 μm. The original austenite grain boundaries are clearly visible, and the martensite grains are dispersed therein. In (a) of comparative example 1, 1654 grains are counted, with equivalent circle diameters ranging from 2.1 to 62.4 μm, and most of the sizes are in the range of 4.55 to 23.8 μm. KAM reflects the degree of local deformation. The green and blue distribution intervals of (d) of embodiment 2 are more than those of (b) of comparative example 2, indicating that embodiment 2 treated with S2 has less residual stress distributed in the grains and is not easy to break when resisting impact. This also proves that the low-temperature impact performance and room-temperature tensile performance of Example 2 are superior to those of Comparative Example 1.

[0071] In summary, the present invention adopts a heat treatment process with the synergistic effect of two steps of preheat treatment and final heat treatment to obtain a composite structure of martensite and ferrite, effectively inhibit the formation and expansion of microcracks, and thus improve the low-temperature impact toughness; further, by selecting a suitable steel chemical composition in this scheme and cooperating with the heat treatment process of this scheme, the best low-temperature impact toughness can be obtained while maintaining good mechanical properties.

[0072] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A heat treatment method for improving the low temperature impact toughness of steel, characterized in that: The steps include: S1. Preheating treatment: heat the steel to 840-880℃, keep it warm for 2-3h, then oil cool it to room temperature; then heat it to 560℃, keep it warm for 8-10h, then oil cool it to room temperature; S2, final heat treatment: the steel is heated to 840°C in the furnace, kept at this temperature for 0.5-1h, then cooled in the furnace to a temperature in the range of Ac1-Ac3 for isothermal treatment, kept at this temperature for 0.5-1h, then water-cooled to room temperature; finally heated to the tempering temperature of 580-600°C, kept at this temperature for 2h, then air-cooled to room temperature.

2. A heat treatment method for improving low temperature impact toughness of steel according to claim 1, characterized in that: The isothermal treatment temperature in step S2 is 730-770°C.

3. A heat treatment method for improving low temperature impact toughness of steel according to claim 1, characterized in that: The steel is for shafting, and its chemical composition includes, by mass percentage, C 0.3-0.4%, Si 0.17-0.37%, Mn 0.5-0.8%, Cr 1.0-1.7%, Ni 1.2-1.6%, Mo 0.2-0.5%, Cu≤0.25%, S≤0.025%, P≤0.025%, and the rest are iron elements and unavoidable impurities.

4. A heat treatment method for improving low temperature impact toughness of steel according to claim 1, characterized in that: The steel is used for shafting, and its chemical composition includes, by mass percentage, C 0.36%, Si 0.27%, Mn 0.61%, Cr1.63%, Ni 1.59%, Mo 0.25%, Cu 0.10%, S≤0.025%, P≤0.025%, and the rest are iron elements and unavoidable impurities.

Citation Information

Patent Citations

  • Heat treatment process capable of improving low temperature impact toughness of 9Ni steel

    CN104745770A

  • Heat treatment process method for improving low-temperature impact toughness of low-carbon low-alloy steel

    CN114959192A

  • Heat treatment method of Ni-free low-carbon microalloyed steel plate

    CN116536491A

  • Heat treatment method for improving low-temperature impact toughness of large 42CrMo steel forgings

    CN116656935A

  • Cr-Mo alloy steel and the manufacturing method of bolt-nut with low temperature used

    KR1019990024462A